Application of Innovative Approach in Hydrology of Ungauged River Catchments for Sustainable Development (A Case Study of River Meroronyi Catchment, Nakuru, Kenya) - Keli, M.; Munyao, T. M.; Ucakuwun, E. K.; Shakala, E. K. (Africa Environmental Review Journal, 2017)
Motivation of the study was the intense degradation of River Meroronyi watershed coupled with continuous changes in land use activities, the environmental importance of the river, where it flows through and a lack of hydrometric gauging network to monitor the river hydrology in response to the catchment environmental conditions. The aim was to set a benchmark for collecting data and information that could be used in planning for sustainable management and development of water resource. Methods used in data collection included visual observation, resource mapping, design of gauging stations along the river, water sampling and measurement of river discharge. Water hydrological data was subjected to laboratory and regression analysis while land use analysis was accomplished by interpretation of landsat images, and photographs of ongoing land use activities. There was a variation in river flow dynamics and suspended sediment concentrations at the selected gauging stations. Results were conclusive as the coefficient of determination between discharge and suspended sediment transport at each gauging site was more than 0.522 which is a statistically significant correlation.